Uterine TPPP3 plays important role in embryo implantation via modulation of β-catenin. Issue 5 (12th June 2018) - Shukla, Vinay; Popli, Pooja; Kaushal, Jyoti Bala; Gupta, Kanchan; Dwivedi, Anila
Abstract: Tubulin polymerization promoting protein 3 (TPPP3) is known to be expressed in the endometrium in a cyclic manner, and its functional role in the physiology of implantation remains unknown. Here we demonstrate a novel function of TPPP3 during the window of implantation and in the establishment of pregnancy using a mouse model. The increased protein expression of TPPP3 and β-catenin during peri-implantation period, i.e. D5 (receptive phase, 0800 h), was observed as compared to that on D1 (nonreceptive phase, 0800 h). SiRNATPPP3 -mediated knockdown of uterine TPPP3 resulted in implantation failure and inhibited the expression of receptivity markers: LIF, Integrin-β3, IHH, and Wnt4. TPPP3 silencing in mouse endometrial epithelial cells also prevented blastocyst attachment and the adhesion reaction. In delayed implantation experiment, expression of TPPP3 was increased in active implantation group (E2 + P4 ) compared to delayed implantation group (P4 ). The increased expression of TPPP3 in E2  + P4 -treated Ishikawa cells compared to vehicle or P4 or E2 alone-treated Ishikawa cells also revealed its upregulation by E2 . The suppression of β-catenin in uterus under the condition of transient knockdown of TPPP3 and the co-immunoprecipitation experiment revealed that regulation of β-catenin was mediated via TPPP3 during implantation. Additionally, in order to gain insight into TPPP3 collaborators, we identified TPPP3 interacting proteins by nanoLC-MS analysis in mouse uterus which might be involved during implantation. In conclusion, our study suggests that TPPP3 is important for embryo implantation and for the establishment of early pregnancy through modulation of β-catenin.